Short note on a Pteranodontoid pterosaur (Pterodactyloidea) from western Queensland, Australia - Kellner,Alexander W.A. (2011)
Flying reptiles from Australia are very rare, represented mostly by isolated bones coming from the Early Cretaceous (Albian) Toolebuc Formation, which crops out in western Queensland. Among the first pterosaur specimens discovered from this deposit is a mandibular symphysis that some authors thought to have a particular affinity to species found in the Cambridge Greensand (Cenomanian) of England. It was further referred as a member of or closely related to one of the genera Ornithocheirus, Lonchodectes or Anhanguera. Here we redescribe this specimen, showing that it cannot be referred to the aforementioned genera, but represents a new species of Pteranodontoid (sensu Kellner 2003), here named Aussiedraco molnari gen. et sp. nov. It is the second named pterosaur from Australia and confirms that the Toolebuc deposits are so far the most important for our understanding of the flying reptile fauna of this country.